Clinicopathological features of papillary thyroid carcinoma in HIV-infected patients - Liu, Jia; Wu, Deqian; Zhu, Jinxin; Dong, Su (Frontiers in Oncology, 2023)
Background Papillary thyroid carcinoma (PTC) is the most common endocrine malignancy, with an increasing incidence over the last decades. Human immunodeficiency virus (HIV)-induced immune deficiency was one of risk factors for cancer tumorigenesis and development. The aim of this study was to describe the clinicopathological features of PTC in HIV-infected patients and discuss possible connections between PTC and HIV infection. Methods A total of 17670 patients from September 2009 to April 2022 who underwent PTC surgery for the first time were analyzed retrospectively. At last, 10 patients of PTC with HIV infection (HIV-positive group) and 40 patients without HIV infection (HIV-negative group) were included. The differences in general data and clinicopathological characteristics between the HIV-positive group and the HIV-negative group were analyzed. Results There were statistically significant differences in age and gender between the HIV-positive group and the HIV-negative group (P<0.05), and males and <55 years old accounted for a higher proportion in the HIV-positive group. The differences in tumor diameter and capsular invasion between the HIV-positive group and HIV-negative group were statistically significant (P<0.05). Meanwhile, in terms of extrathyroid extension (ETE), lymph node metastasis and distant metastasis, the HIV-positive group were significantly higher than the HIV-negative group (P<0.001). Conclusion HIV infection was a risk factor for larger tumors, more severe ETE, more lymph node metastasis, and more distant metastasis. HIV infection could promote PTC proliferation and make PTC more aggressive. Many factors such as tumor immune escape, secondary infection, etc. may are responsible for these effects. More attention and more thorough treatment should be paid to these patients.